The Consumption Paradigm in Marketing - Ardianto, Eka (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2003)
This article elaborates consumption paradigm in marketing. In background, this paper reviews different perspectives of consumption: economic perspective and marketing perspective. In ontology, this work describes various issues regarding consumption view. In epistemology, this article demonstrates how marketers especially researches explore the consumption phenomena. In methodology, the article describes experiential marketing âone of applied consumption paradigm in marketing, which could be an alternative choice of marketing practices.